Diseño de modelo de gestión para las empresas dedicadas a la importación y distribución de repuestos y accesorios para la industria petrolera caso Kemar International LLC - Calero Sánchez, Álvaro Fabricio (2013)
This project has as central objective "To design a management model for the company Kemar International in Quito city in order to present a global vision oriented to the internal and external customer". The importance of practicing a proper management will allow an excellent managing of all the resources of the company. The thesis begins with the recovery of theoretical basis about management and business excellence, foundations of services, imports, internal control of processes and human talent management, which will serve as basis for the design of the proposed model.